The Burden of Breast Cancer Predisposition Variants Across The Age Spectrum Among 10 000 Patients. Issue 5 (23rd April 2019) - Chavarri‐Guerra, Yanin; Hendricks, Carolyn B.; Brown, Sandra; Marcum, Catherine; Hander, Mary; Segota, Zdenka E.; Hake, Chris; Sand, Sharon; Slavin, Thomas P.; Hurria, Arti; Soto‐Perez‐de‐Celis, Enrique; Nehoray, Bita; et al.
Abstract : BACKGROUND/OBJECTIVES: Women diagnosed with breast cancer (BC) at an older age are less likely to undergo genetic cancer risk assessment and genetic testing since the guidelines and referrals are biased toward earlier age at diagnosis. Thus, we determined the prevalence and type of pathogenic cancer predisposition variants among women with a history of BC diagnosed at the age of 65 years or older vs younger than 65 years. DESIGN: Prospective registration cohort. SETTING: The Clinical Cancer Genomics Community Research Network, including 40 community‐based clinics in the United States and 5 in Latin America. PARTICIPANTS: Women with BC and genetic testing results. MEASUREMENTS: Sociodemographic characteristics, clinical variables, and genetic profiles were compared between women aged 65 years and older and those younger than 65 years at BC diagnosis. RESULTS: Among 588 women diagnosed with BC and aged 65 years and older and 9412 diagnosed at younger than 65 years, BC‐associated pathogenic variants (PVs) were detected in 5.6% of those aged 65 years and older (n = 33) and 14.2% of those younger than 65 years (n = 1340) ( P < .01). PVs in high‐risk genes (eg, BRCA1 and BRCA2 ) represented 81.1% of carriers among women aged 65 years and older (n = 27) and 93.1% of those younger than 65 years (n = 1248) ( P = .01). BRCA2 PVs represented 42.4% of high‐risk gene findings for those aged 65 years and older, whereas BRCA1 PVs were most common among carriers younger than 65 years (49.7%). PVs (n = 7) in moderate‐risk genes represented 21.2% for carriers aged 65 years and older and 7.3% of those younger than 65 years (n = 98; P < .01). CHEK2 PVs were the most common moderate‐risk gene finding in both groups. CONCLUSION: Clinically actionable BC susceptibility PVs, particularly in BRCA2 and CHEK2, were relatively prevalent among older women undergoing genetic testing. The significant burden of PVs for older women with BC provides a critical reminder to recognize the full spectrum of eligibility and provide genetic testing for older women, rather than exclusion based on chronological age alone. J Am Geriatr Soc 67:884–888, 2019.